Financial Development, Inequality and Poverty : Some International Evidence - Ben Naceur, Sami (IMF Working Papers; Working Paper ;, 2016)
This paper provides evidence on the link between financial development and income distribution. Several dimensions of financial development are considered: financial access, efficiency, stability, and liberalization. Each aspect is represented by two indicators: one related to financial institutions, and the other to financial markets. Using a sample of 143 countries from 1961 to 2011, the paper finds that four of the five dimensions of financial development can significantly reduce income inequality and poverty, except financial liberalization, which tends to exacerbate them. Also, banking sector development tends to provide a more significant impact on changing income distribution than stock market development. Together, these findings are consistent with the view that macroeconomic stability and reforms that strengthen creditor rights, contract enforcement, and financial institution regulation are needed to ensure that financial development and liberalization fully support the reduction of poverty and income equality.